No association of Vitamin D pathway genetic variants with cancer risks in a population-based cohort of German older adults - Ordóñez Mena, José M.; Schöttker, Ben; Saum, Kai-Uwe; Burwinkel, Barbara; Brenner, Hermann (Cancer epidemiology, biomarkers & prevention, 2017)
Background: Several investigations assessed the association of vitamin D receptor (VDR) SNPs with cancer risk. Less is known about the implications of other vitamin D pathway SNPs on cancer risk. Methods: In a population-based cohort study of 9,949 German older adults, we used Cox regression to assess the association of 6 SNPs in the VDR, vitamin D-binding protein (GC), 7-dehydrocholesterol reductase (DHCR7), vitamin D 25-hydroxylase (CYP2R1), and vitamin D 24-hydroxylase (CYP24A1) genes with total and site-specific cancer incidence endpoints. Results: Overall, no association of SNPs with cancer incidence endpoints was observed, except for a genotype score based on SNPs associated with lower 25(OH)D, which was associated with higher lung cancer risk [HR, 1.20; 95% confidence intervals (CI), 1.03-1.39], although this was no longer significant after correcting for multiple testing. Conclusions: Our data provide little to no evidence of a major influence of vitamin D genetic predisposition on cancer risks. Impact: Large-scale genetic epidemiology consortia and meta-analysis of smaller published studies are needed to verify a potential modest influence of genetic variation in the association of vitamin D with the risk of cancer.